Video recording emergency care and video-reflection to improve patient care; a narrative review and case-study of a neonatal intensive care unit - Heesters, Veerle; Witlox, Ruben; van Zanten, Henriette A.; Jansen, Sophie J.; Visser, Remco; Heijstek, Veerle; Te Pas, Arjan B. (Frontiers in Pediatrics, 2022)
As the complexity of emergency care increases, current research methods to improve care are often unable to capture all aspects of everyday clinical practice. Video recordings can visualize clinical care in an objective way. They can be used as a tool to assess care and can be used to reflect on care with the caregivers themselves. Although the use of video recordings to reflect on medical interventions (video-reflection) has increased over the years, it is still not used on a regular basis. The use of video-reflection in emergency care can provide an objective view on the technique of interventions performed and the clinical effect. Video-reflection has educational value and can improve teams’ management and performance. It has a positive effect on guideline adherence, documentation, clinical care and teamwork. Video-reflection can also be focused on the caregivers; during video-reflexive ethnography sessions they review recordings together to reflect on their everyday practice, to improve care. Recordings provide a full overview of an intervention and can be used to identify latent safety threats to patient safety. Although video-reflection in emergency care has proven to be valuable, certain preconditions have to be met and obstacles need to be overcome. These include gaining trust of the caregivers, having a proper consent-procedure, maintaining confidentiality and adequate use of technical equipment. To implement the lessons learned from video-reflection in a sustainable way and to continuously improve care, it should be integrated in regular simulation training or education. It is important to address these aspects before implementing video reflection as standard care. This review describes the development of video recording in emergency care and how video-reflection can improve patient care and safety in new ways.